Decree of the president of the Arab Republic of Egypt No. 276 of the year 2004 Concerning the Approval of the Convention for the Unification of Certain Rules for International Carriage by Air as signed In Montreal On 28/5/1999 - Egypt (2025)
Decree of the President of the Arab Republic of Egypt No. 276 of the Year 2004 concerning the approval of the agreement of the convention for the Unification of certain rules for international carriage by air as signed in Montreal 28/5/1999 – Decree of the Minister of Foreign Affairs No. 17 of the year 2005 قرار رئيس جمهورية مصر العربية رقم 276 لسنة 2004 بشأن الموافقة على اتفاقية توحيد بعض قواعد النقل الجوى الدولى، والموقعة فى مونتريال فى 28/5/1999 – قرار وزير الخارجية رقم 17 لسنة 2005